SELF-COMPACTING CONCRETE WITH THE USE OF PLANT WASTE - R. S. Fediuk; A. V. Mochalov; D. N. Pezin; R. A. Timokhin (Вестник СибАДИ, 2018)
Introduction. The development of efficient self-compacting concrete is an urgent task for building materials science. A successful implementation of the task can be the use of ash of rice husk as an alternative material in the production of concrete. The aim of the research is to study the influence of the organo-mineral nanomodifier on the properties of self-compacting concrete.Materials and methods. The organomineral nanomodifier is developed using Portland cement, rice husk ash and quartz flour, which are milled together to a specific surface of 500-900 m2 /kg. Superplasticizer “Hidetal” is used to reduce the water-cement ratio. The properties of the mixture are tested for rheological characteristics. The bulk density of the samples is measured by the Archimedes method. An investigation of the concrete microstructure is carried out by electron microscopy. The compressive strength of the samples is obtained at the age of 7 and 28 days.Results. The most effective fineness of grinding of nanomodifier is 550 m2 /kg. The maximum increase in strength and the best rheological characteristics in comparison with pure thin-grained Portland cement are achieved by the introduction of a nanomodifier in an amount of 10.5%. However, the variation in the modulus of the samples’ elasticity does not reveal the dependence on the amount of nanomodifier. The modulus of elasticity of self-compacting concrete primarily depends on the amount of coarse aggregate. Therefore, the pozzolanic reaction helps to increase the compressive strength of concrete by improving the interfacial bond between the cement paste and the aggregate.Discussion and conclusions. Plant waste has the potential to be used as a replacement for Portland cement in self-compacting concrete that retains the mechanical and operational characteristics of the concrete mix and ready-mixed concrete. The surface area of the ash is increased by mechanochemical activation. The inclusion of ash led to a reduction in the workability of concrete, but with the help of an additional superplasticizer, these properties for all samples are aligned. An increase in the nanomodifier content leads to a decrease in the early physical and mechanical properties, while the final strength of self-compacting concrete containing a nanomodifier is comparable to conventional samples.